2009
DOI: 10.1016/j.cellbi.2008.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia pneumoniae induces macrophage‐derived foam cell formation via PPAR α and PPAR γ‐dependent pathways

Abstract: In the presence of low density lipoprotein (LDL), Chlamydia pneumoniae induces macrophage-derived foam cell formation, a typical pathological feature of early atherosclerosis. However, its mechanism has not been fully understood. Peroxisome proliferator-activated receptors (PPARs) are key regulators of macrophage lipid metabolism. This study therefore investigated the role that PPAR alpha and PPAR gamma may play a role in C. pneumoniae-induced foam cell formation. Oil Red O staining and Lipid mass quantificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 38 publications
(44 reference statements)
0
30
1
1
Order By: Relevance
“…Although PPARγ has been extensively investigated for its role in other diseases (10), its immunoregulatory role(s) in infectious diseases is just now being recognized (4649). There are two recent reports for altered PPARγ levels during mycobacterial infection in humans, both involving the attenuated BCG.…”
Section: Discussionmentioning
confidence: 99%
“…Although PPARγ has been extensively investigated for its role in other diseases (10), its immunoregulatory role(s) in infectious diseases is just now being recognized (4649). There are two recent reports for altered PPARγ levels during mycobacterial infection in humans, both involving the attenuated BCG.…”
Section: Discussionmentioning
confidence: 99%
“…The ultrastructural observations provided morphological evidence that C. pneumoniae might not only survive but also develop in macrophages in human atherosclerotic lesions. In accordance with this, in vitro experiments showed that C. pneumoniae infection of monocytes induces their differentiation into macrophages [8,[31][32][33] . The mechanisms by which C. pneumoniae might affect macrophage function have been examined [8,33,36,[70][71][72][73] and it has been also shown that infection of macrophages with C. pneumoniae in vitro accelerates foam cell formation [24,[30][31][32][33][73][74][75][76] .…”
Section: Discussionmentioning
confidence: 50%
“…It has been reported that C. pneumoniae infection accelerates macrophage foam cell formation in vitro through the stimulation of low-density lipoprotein (LDL) oxidization and entry of atherogenic LDL to the cytoplasm, indicating that the microorganism represents a causative agent in atherosclerosis [31][32][33] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The purified mycobacterial cell wall lipoprotein P19 is well-defined as a TLR2 agonist (23). PPARγ is a prime candidate for an intracellular molecular switch based on its central role in controlling the inflammatory response in macrophages (24), and although PPARγ has been extensively investigated in other diseases (25), its immunoregulatory role in infectious diseases (particularly tuberculosis) is just beginning to be recognized (8,26,27). In the present study, the expression of PPARγ in human macrophages was enhanced by M.tb H37Rv and P19, but not M. smegmatis.…”
Section: A B C D Discussionmentioning
confidence: 99%